Dynamic Response and Numerical Interpretation of Three Kinds of Metals for EFP Liner under Explosive Loading - Li Ding; Peihui Shen; Liuqi Ji (Crystals, 2022)
In order to study the dynamic response of tungsten heavy alloy materials under explosive loading, two kinds of typical tungsten alloys for explosively formed projectile (EFP) liner and one kind of existing EFP liner were tested in a flash X-ray experiment, with copper liner as a reference. Results showed that copper liner could form a coherent EFP, while 90W–9Ni–Co and W–25Re liners fractured to different extents. The microscopic features of the three kinds of metals were examined and compared with the original liner, and the microstructure evolutions under explosive loading were analyzed with the fracture model and mechanism of the two kinds of tungsten alloys’ fracture determined. Associated with the stress and strain conditions by numerical simulation, the fracture mechanism of tungsten heavy alloys can be analyzed. The crack-tip plastic zones of 90W–9Ni–Co and W–25Re are much smaller than copper, and due to the severe stress concentration at the tip of cracks, it is easy for cracks to propagate and trigger the cleavage in tungsten alloys. The value of a crack-tip plastic zone r(θ) can be used to explain the fracture phenomenon in explosive loading, which can be an alternative guideline for the material selection criteria of the EFP liner. The research results are significant in understanding the dynamic forming, microstructure evolution, and fracture mechanism of tungsten heavy alloys.